New Kingdom ostraca from the Fitzwilliam Museum, Cambridg e - Hagen, Fredrik. (Culture and History of the Ancient Near East, 2011)
This book publishes a previously unknown collection of hieratic ostraca from the Fitzwilliam Museum, Cambridge. The texts include a broad range of genres, including wisdom literature, religious hymns, magical texts, medical recipes, private letters, administrative notes, scribal exercises ( Kemit ), and copies of tomb inscriptions. Each ostracon is presented with photographs, facsimile drawings and hieroglyphic transcriptions, as well as translations and brief philological commentaries. Many of the texts can be linked to the village of Deir el-Medina on internal evidence, and the book offers new data to scholars working with material from this famous site.